2009
DOI: 10.1177/1065912909336271
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of State Judicial Structures on Citizen Litigiousness

Abstract: Some researchers argue over the existence of a “litigation explosion,” while others seek to understand the causes of variation in citizen legal mobilization and rates of litigation among states. Existing studies have provided important insight into citizens’ propensity to invoke the state courts to settle disputes; however, there remain unresolved questions concerning state litigation rates. The authors argue that the structural aspects of state judicial systems, specifically the professionalism of the courts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…Another study (Helland and Tabarrok 2002;Tabarrok and Helland 1999) looked at the possible impact of selection system on awards in tort cases, and reported that the awards were higher in states where trial judges were elected in partisan elections; however, given that the awards were made by juries, it is not altogether clear what the causal mechanism might be linking judicial selection to jury awards. A third study (Yates et al 2010) The regression model included control variables for type of tort, type of legal issue, absence of an intermediate appellate court that normally handled first appeals in tort cases, whether one of the parties was a governmental unit (presumably almost always as a defendant), the number of tort reform measures in effect in the state, and justice's ideology.…”
Section: Tort Casesmentioning
confidence: 99%
“…Another study (Helland and Tabarrok 2002;Tabarrok and Helland 1999) looked at the possible impact of selection system on awards in tort cases, and reported that the awards were higher in states where trial judges were elected in partisan elections; however, given that the awards were made by juries, it is not altogether clear what the causal mechanism might be linking judicial selection to jury awards. A third study (Yates et al 2010) The regression model included control variables for type of tort, type of legal issue, absence of an intermediate appellate court that normally handled first appeals in tort cases, whether one of the parties was a governmental unit (presumably almost always as a defendant), the number of tort reform measures in effect in the state, and justice's ideology.…”
Section: Tort Casesmentioning
confidence: 99%
“…We opted to specify them as individual dummy variables 16 . We selected this approach over creation of an additive index of the number of reforms present in a state (Yates et al. 2009) because such indexes treat the marginal effect of each additional reform as equal, an assumption not supported by the existing literature on the effects of malpractice reforms on claims and premiums (Mello 2006; Thorpe 2004).…”
Section: Data and Variablesmentioning
confidence: 99%
“…We opted to specify them as individual dummy variables. 16 We selected this approach over creation of an additive index of the number of reforms present in a state (Yates et al 2009) because such indexes treat the marginal effect of each additional reform as equal, an assumption not supported by the existing literature on the effects of malpractice reforms on claims and premiums (Mello 2006;Thorpe 2004). We also rejected the approach of developing a scale ranking tort reforms according to their likely efficacy (Waters et al 2003) because the available evidence base is insufficient to support such judgments concerning the relative effects of malpractice reforms on birth outcomes.…”
Section: Tort Reformsmentioning
confidence: 99%
“…Probably the most widely used approach to assessing claiming patterns is to examine litigation rates (number of cases per some unit of population). There have been longitudinal studies at both national and subnational levels (Grossman and Sarat 1975, McIntosh 1980-81, Daniels 1982, Daniels 1984, Daniels 1985, McIntosh 1989, Van Loon and Langerwerf 1990, Wollschläger 1990, Wollschläger 1997, cross-national studies (Galanter 1983, Blankenburg 1992, Blankenburg 1998, Wollschläger 1998, and at least in the United States studies comparing subnational units (Grossman et al 1982, Yates et al 2001, Jacobi 2009, Yates et al 2010. Some of the studies are purely description, documenting differences and trends in litigation rates (i.e., patterns of secular increase, cyclical patterns, etc.…”
Section: Dispute Processingmentioning
confidence: 99%
“…Medical malpractice is one area where the filing of lawsuits is probably a reasonably good proxy for claim filing because the overwhelming majority of such claims end up in suit if they survive the initial screening by a lawyer. There is a significant body of research that examines the impact of institutional and political factors on the filing of lawsuits (Lee et al 1994, Di Pietro and Carns 1996, p. 63, Schmit et al 1997, Browne and Puelz 1999, Yates et al 2001, Browne and Schmit 2008, Jacobi 2009, Yates et al 2010. 29 Morris (2007, p. 353) reports that "of over 2,000 reports in the (English) national press since 1993 featuring the term 'compensation culture, all but nineteen of them appeared after 1998.…”
mentioning
confidence: 99%